Observation of The Relationship Between Play Activities and Language Development in Children Aged 3-5 Years and The Role of Parents. - Fitria, Yoza; Ivan Achmad Nurcholis (Indonesian Journal Of Education, 2025)
Observation of the Relationship Between Play Activities and Language Development in Children Aged 3-5 Years and the Role of Parents Language development in early childhood is crucial as it influences children's cognitive, social, and emotional abilities. Between the ages of 3 and 5, children undergo significant changes in their understanding and use of language. This process involves not only vocabulary expansion but also the acquisition of grammar and communication skills. One effective way to support language development is through play. Imaginative, constructive, and social play provides opportunities for children to experiment with language in enjoyable contexts. Activities such as role-playing, puzzles, guessing games, singing, and counting stimulate both language skills and memory. In this observation, environments such as home and preschool are shown to greatly influence how children learn and interact with language. Through play that involves verbal interaction, children naturally develop their language skills in a fun and engaging way. Therefore, the role of parents and educators in creating a language-rich play environment is essential in supporting language development during early childhood.